A recommended training program for developing cervical muscles strength and its effect on performance effectiveness of defense against bridge block and waist turnover - Fawzy Al-Bedewy, E.; Hosny Al-Shorbagy, N. (World Journal of Sport Sciences, 2010)
Bridging is one of the basic wrestling skills as it is used in defense or attack. This skill is directly dependant on neck muscles as over-arching helps in better results either in attack or in defense. This research aimed at designing a training device for cervical muscles strength to be used in a training program, identifying the effect of the training program on developing cervical muscles strength and identifying the effect of the training program on developing the technical performance of bridge block and waist turnover. Sample was purposefully chosen from Gharbia Greco-roman Wrestling Team (16 wrestlers) and divided randomly into two groups (8 wrestlers each) to form the experimental and control group. The researchers used the quasiexperimental approach. Results showed statistical significant differences between the control and experimental groups on the post-tests in favor of the experimental group. The recommended program is characterized by calibrating exercises according to the individual differences and abilities of each wrestler. This allowed for adaptation and development of cervical muscles strength. The increase in cervical muscles strength, in turn, led to performing bridges more effectively as support was on the feet from one point and the forehead from the other. This increases the load on cervical muscles. With the increase of cervical muscles strength, there was a correspondent increase in performing bridges. The researchers recommend the use of the recommended training program and the device for developing cervical muscles strength.